The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1590/s0036-46651988000600006
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Clostridium difficile nas fezes de crianças do Rio de Janeiro, RJ

Abstract: A ocorrência de Clostridium difficile foi analisada em amostras de fezes de 175 crianças com idade variando de 1 a 35 meses. Para o isolamento primário do microrganismo foi empregado o meio de cultura seletivo diferencial "CCFA" (cicloserina-cefoxitina-frutose-agar). Num grupo de 67 crianças sem distúrbios gastrintestinais e que não estavam sob uso de agentes antimicrobianos a ocorrência do C. difficile foi de 22,4%, enquanto que num outro grupo de 28 crianças nas mesmas condições, porém, sob tratamento com an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Similarly, Soyletir et al (1996) found this organism in 4.9% of Turkish children with diarrhea. In Brazil, Garcia and Uzeda (1988) isolated C. difficile from 13.8% of clinical samples from hospitalized children with acute diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Soyletir et al (1996) found this organism in 4.9% of Turkish children with diarrhea. In Brazil, Garcia and Uzeda (1988) isolated C. difficile from 13.8% of clinical samples from hospitalized children with acute diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, there are few epidemiological studies involving this pathogen as a cause of diarrhea in children [4, 8]. Since a stool sample harbored the profile of toxigenicity tcdA+/tcdB− and another cdtA+/cdtB+ , it suggested a low circulation of toxigenic C. difficile in Brazilian children, and the acute diarrhea in children could have been caused by other enteropathogens than C. difficile , like typical viral or bacterial pathogens, such as Norovirus , Rotavirus , Salmonella , or Campylobacter , and this needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%